1975
DOI: 10.1099/00221287-88-1-141
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Large-scale Synchronous Cultures of the Trypanosomatid, Crithidia fasciculata, by Cell-size Selection: Changes in Respiration and Adenylate Charge through the Cell-cycle

Abstract: S U M M A R YLarge-scale synchronous cultures of Crithidia fasciculata were prepared by a sedimentation-velocity-size-selection method using a non-osmotic gradient in a zonal rotor. Synchrony indices of up to 0.68 were obtained (average length of cell-cycle, 5-1 h). Dry weight, protein and RNA increased continuously so as to double in one cell-cycle. Rates of oxygen uptake/ml culture increased overall so as to double over a cell-cycle, but rose to maxima at five periods in the cellcycle. KCN gave a similar deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

1977
1977
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
18
2
Order By: Relevance
“…These respiratory oscillations are clearly different from those previously observed in synchronous cultures of the fission yeast Schizosaccharomyces pombe (growing in the presence of glucose), where a Pasteur effect was invoked to explain the modulation of mitochondria1 activity (Poole et al, 1973), in the trypanosomatid protozoon Crithidia fasciculata (Edwards et al, 1975), or in Tetrahymena pyriformis . The observation of a dramatic fluctuation of adenylate energy charge in the trypanosome (Edwards et al, 1975), in T. pyriformis , and in A .…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…These respiratory oscillations are clearly different from those previously observed in synchronous cultures of the fission yeast Schizosaccharomyces pombe (growing in the presence of glucose), where a Pasteur effect was invoked to explain the modulation of mitochondria1 activity (Poole et al, 1973), in the trypanosomatid protozoon Crithidia fasciculata (Edwards et al, 1975), or in Tetrahymena pyriformis . The observation of a dramatic fluctuation of adenylate energy charge in the trypanosome (Edwards et al, 1975), in T. pyriformis , and in A .…”
Section: Resultscontrasting
confidence: 42%
“…The observation of a dramatic fluctuation of adenylate energy charge in the trypanosome (Edwards et al, 1975), in T. pyriformis , and in A . castellanii (this report) is of great interest as it has been suggested that thermodynamic and kinetic considerations of the regulatory mechanisms involved in energy metabolism would predict considerable constraints on variations of this parameter, and a tendency to stabilization of adenylate charge between values of 0.87 and 0.95 (Chapman & Atkinson, 1977).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiroplasma citri, like many other organisms (Bomsel & Pradet, 1968;Chapman et al, 1971 ;Niven et al, 1977), maintained its energy charge at high values close to 0.9 throughout active growth, though some eukaryotic organisms have been reported to have low energy charge values even when actively metabolizing (Edwards et al, 1975;Edwards & Lloyd, 1977;Lloyd et al, 1978). The importance of energy charge as a metabolic regulator in vivo is still under debate (Atkinson, 1977;Fromm, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Intensification factors of 3.7, 6.1 and 13.3 for c, b and a-type cytochromes respectively (Edwards et al, 1977) were used to quantify low temperature spectra. Measurements of adenine nucleotide levels were as described by Edwards, Statham & Lloyd (1975) using luciferase assays on extracts from I ml of culture prepared by chloroform extraction. ATP, ADP and AMP were estimated by the method of Chapman, Fall & Atkinson (1971) using ATP as a calibration standard.…”
Section: E T H O D Smentioning
confidence: 99%